2003
DOI: 10.1002/app.13028
|View full text |Cite
|
Sign up to set email alerts
|

Influence of titanium dioxide on crystallization behavior of an ethylene–propylene copolymer

Abstract: ABSTRACT:Crystallization of an ethylene-propylene copolymer (E/P) filled with diverse weight percentages of titanium dioxide (TiO 2 ) was performed under isothermal and nonisothermal conditions to investigate the influence of the inorganic substance on the nucleation and growth mechanisms of the matrix. The overall and radial crystallization rates of the composite materials were measured using, respectively, differential scanning calorimetry (DSC) and optical microscopy. The nucleation density of E/P spherulit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…In contrast, Burke et al observed an increase in the crystallization rate of TiO 2 ‐filled PP, but they did not find any change in the spherulite growth rate 8. Similar results were obtained by Raimo et al in which the addition of TiO 2 particles to ethylene‐propylene copolymer promoted the nucleation 9. At a high crystallization temperature, the spherulite growth rate was unchanged whereas at a low crystallization temperature the spherulite growth rate was higher than that of neat copolymer.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In contrast, Burke et al observed an increase in the crystallization rate of TiO 2 ‐filled PP, but they did not find any change in the spherulite growth rate 8. Similar results were obtained by Raimo et al in which the addition of TiO 2 particles to ethylene‐propylene copolymer promoted the nucleation 9. At a high crystallization temperature, the spherulite growth rate was unchanged whereas at a low crystallization temperature the spherulite growth rate was higher than that of neat copolymer.…”
Section: Introductionsupporting
confidence: 58%
“…8 Similar results were obtained by Raimo et al in which the addition of TiO 2 particles to ethylene-propylene copolymer promoted the nucleation. 9 At a high crystallization temperature, the spherulite growth rate was unchanged whereas at a low crystallization temperature the spherulite growth rate was higher than that of neat copolymer. Wang et al showed that the manipulation of the interfacial properties of BaSO 4 microparticles using different chemical modifiers could alter the interfacial interaction between PP and BaSO 4 and hence the PP spherulite growth rate.…”
Section: Introductionmentioning
confidence: 96%
“…12,13 Deterministic nucleation has been observed even in thin specimens, 9,14 and it has been proved that thicker samples crystallized in DSC pans consist of superimposed layers of bi-dimensional spherulites. 2,4 Despite the dependence of the nucleation modality on the thickness, the method herein proposed is applicable not only to thin, but also to thick samples provided that spherulites nucleated at the beginning of the solidification on the top surface of the DSC crystallized specimens are present.…”
Section: Resultsmentioning
confidence: 99%
“…3 It may also happen that additives with high refractive indices hinder the observation of polymer samples under lighttransmission microscopes, making the use of the classic method for growth rate measurements impossible. 4 Furthermore, if spherulites with different growth rates arise in various concentrations during solidification (as for polymorphs and polymer blends), the conventional measure of growth rates may not be easy, especially for less abundant spherulite types. Usually, to measure growth rates of different crystalline forms, it is necessary to add specific nucleating agents, although these foreign substances could affect the crystallization kinetics of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters become important when the spherulitic growth is considered, especially the interactions between the matrix and the reinforcement. Regarding this, Raimo and Martuscelli20 showed that clay can produce an increase in the spherulitic growth rate at low temperatures but no changes at high temperatures. Wang et al21 demonstrated that the spherulitic growth rate was reduced when the filler–polymer interaction was weak and even more when it was stronger in the case of BaSO 4 ‐filled polypropylene.…”
Section: Introductionmentioning
confidence: 99%